RADIOCARBON INVESTIGATION OF THE BIG BAOBAB OF OUTAPI, NAMIBIA - PATRUT, Adrian; PATRUT, Roxana T.; RAKOSY, Laszlo; RAKOSY, Demetra; RATIU, Ileana-Andreea; VON REDEN, Karl F. (Studia Universitatis Babeș-Bolyai Chemia, 2021)
The article reports the AMS (accelerator mass spectrometry) radiocarbon dating results of the Big baobab of Outapi, which is the largest African baobab of Outapi, Namibia. The investigation of this monumental baobab revealed that it consists of 8 fused stems, out of which 4 are false stems. The Big baobab exhibits a closed ring-shaped structure. Three stems build the ring, which is now incomplete due to previous damage to the false cavity. Three wood samples were collected from the false cavity and from the longest false stem. Seven segments were extracted from the samples and dated by radiocarbon. The oldest investigated sample segment had a radiocarbon date of 820 ± 17 BP, corresponding to a calibrated age of 780 ± 10 calendar years. According to dating results, the Big baobab of Outapi is 850 ± 50 years old.